Tunable piezoelectric generator coupled with Shape Memory Alloy (SMA) heat engine as thermal energy harvester - Hassan, Hamdan; Wahid, Azni Nabela; Abdul Muthalif, Asan Gani (IET, 2022)
With the ever-growing energy demand and environmental concerns, research on alternative energy is vital for sustainability. Thermal energy harvesting using shape memory alloy (SMA) heat engine is one of the possible methods for power generation from low to high-grade thermal energy but suffers from low performance; one of the reasons is due to the varying angular velocity input. In this research, a tunable generator coupled with a pulley-type SMA heat engine is designed to produce output voltage at different resonances, matching with the varying frequency input from the heat engine. The generator consists of piezoelectric cantilever beams arranged around a pulley with moving supporting clamps to manipulate their natural frequencies. The generators are mechanically excited by repulsive forces of magnets attached at both rotating SMA heat engine and generator pulleys. Results show that the peak output voltage produced by the tuned piezoelectric generator is higher as compared to untuned where the percentage of improvement is 230.62%, 44.75%, 11.59%, 76% and 96.83%, at 40mm, 45mm, 50mm, 55mm and 60mm effective length, respectively. Results from this study can help to design an SMA heat engine coupled with piezoelectric generators where maximum voltage can be generated consistently for a more efficient thermal energy harvesting.